Regulatory T Cells in Allergy and Asthma - Martín-Orozco, Elena; Norte-Muñoz, María; Martínez-García, Javier (Frontiers in Pediatrics, 2017)
The immune system correct functioning requires a sophisticated equilibrium between response to continuous microbial challenges, and tolerance to harmless antigens, like self-antigens, food antigens, commensal microbes, allergens, etc. When this equilibrium is altered, it can guide to inflammatory disorders, tumor growth, autoimmunity, and allergy/asthma. The objective of this review is to show the existing data on the importance of regulatory T cells (Tregs) on this balance and to underline how intrauterine and early life environmental exposures influence the maturation of the human immune system. Genetic and environmental factors during embryo development and/or early life will result in a proper or, by contrary, inadequate immune maturation with either beneficial or deleterious effects on health. We have focus here in Tregs as a reflection of the maturity of the immune system. We explain the types, origins and the mechanisms of action of these cells discussing their role in allergy and asthma predisposition. A better understanding of the role of Tregs in counteracting dysregulated immunity would provide approaches to diminish asthma and other related diseases in infants.